Case Report on Secondary Peritonitis Caused by Jejunum Perforation - Pokhrel, Amrit Prasad; Neupane, BR; Gupta, S; Upreti, S; Shrestha, A (Journal of Gandaki Medical College-Nepal, 2017)
The small intestine is third in frequency intraperitoneal organ injured after blunt trauma of abdomen. Peritonitis caused by isolated jejunum perforation is very rare. As most of these cases are accompanied with injuries with other structures in the abdomen, hence it is not suspected. Therefore failure in diagnosis and delay in treating these injuries significantly increase the morbidity and mortality of these patients. Here, we report a case of a 60 year old gentleman admitted in surgery department with severe abdominal pain, multiple episodes of vomiting followed to fast breathing and reduced consciousness. Our patient presented in septic shock, with toxic looks and clear cut rigid abdominal wall. To the best of our knowledge this is the first time we describe a case report on isolated jejunum perforation as a result of physical assault. Journal of Gandaki Medical College Vol. 10, No. 1, 2017, Page: 57-58